The sources of renewed national dynamism - Mazarr, Michael J. 1965- (Rand Corporation, 2024)
"History is full of great powers that hit a peak of competitive power and then stagnate and eventually decline. There are fewer cases of great powers that have confronted such headwinds and managed to generate a repeated upward trajectory--to renew their power and standing in both absolute and relative terms. Arguably, that is precisely the challenge that faces the United States. Its competitive position is threatened both from within (in terms of slowing productivity growth, an aging population, a polarized political system, and an increasingly corrupted information environment) and outside (in terms of a rising direct challenge from China and declining deference to U.S. power from dozens of developing nations). Left unchecked, these trends will threaten domestic and international sources of competitive standing, thus accelerating the relative decline in U.S. standing. In this report, the authors shed light on this challenge by examining the problem of national decline and renewal. It is part of a larger study on the societal determinants of a nation's competitive position, which has nominated several key qualities that determine a society's competitive success and failure. The findings of the first phase of the study suggest that it is very difficult for countries to achieve multiple periods of efflorescence or national peak dynamism. This report is one of several independent second-phase analyses on distinct topics that examine the prospects for the United States to do so, combining historical case analysis with contemporary assessments."
Keywords: Großmacht; Erneuerung; Zusammenbruch; Balance of power; Great powers; United States / Foreign relations; Community Resilience; International Economic Relations; Military Affairs; Russia; Security Cooperation; United Kingdom; United States; HISTORY / Europe / General; HISTORY / United States / General; POLITICAL SCIENCE / International Relations / Treaties; POLITICAL SCIENCE / Political Economy; POLITICAL SCIENCE / Political Freedom; POLITICAL SCIENCE / Terrorism